Fine needle aspiration cytology of palpable supraclavicular lymph nodes - RC Adhikari; A Jha; G Sayami; G Shrestha; SK Sharma (Journal of Pathology of Nepal, 2011)
Background: Fine needle aspiration cytology as a first line of investigation has assumed importance in diagnosing a variety of disease process. The aim of this study was to assess the diagnostic value of fine needle aspiration cytology in the evaluation of palpable supraclavicular lymph nodes. Materials and methods: This was a retrospective study of fine needle aspiration cytology of palpable supraclavicular lymph node done between January 1, 2007 and December 31, 2009. Fine needle aspiration cytology was performed on 149 patients (49 cases at Om Hospital & Research Centre and 100 cases at Tribhuvan University Teaching Hospital). Results: The right supraclavicular lymph node was enlarged in 55% cases, while the left supraclavicular lymph node alone was palpable in 40.3% cases and in 7 of 149 (4.7%) cases, bilateral supraclavicular lymph nodes were palpable. Cytological diagnoses were categorized as reactive (8.7%), tuberculosis (41.6%), lymphoma (4.8%) and metastasis (44.9%). Of a total of 74 cases of malignancy, 90.5% were non-lymphoid and 9.5% were lymphoid (5 Non-Hodgkin lymphoma and 2 Hodgkin lymphoma). Of the 67 cases of metastatic disease, three major types of malignancy found in supraclavicular lymph nodes were Squamous cell carcinoma (28 cases), adenocarcinoma (21 cases) and others (small cell carcinoma, papillary thyroid carcinoma etc). Adenocarcinoma tended to metastasize to the left supraclavicular lymph node. Lung was the most common primary site (43.3%), followed by stomach, ovary, breast and larynx. However, in 28.4% cases, no primary site was found. Conclusion: The fine needle aspiration cytology can be used as a first line investigation in the evaluation of supraclavicular lymphadenopathy due to its low cost, simplicity and minimal invasiveness. Keywords: Supraclavicular lymph node; Fine needle aspiration cytology; Metastasis DOI: 10.3126/jpn.v1i1.4441 Journal of Pathology of Nepal (2011) Vol.1, 8-12